Ästhetik der leisen Töne : Die visuelle Vorstellungswelt westdeutscher Verlage in der buchwerbung der 1950er Jahre - Kemnitz, Malva (Buchwissenschaftliche Beiträge aus dem Deutschen Bucharchiv München, 2013)
Aesthetics and visualizations of an era often say more about its society and culture than some written sources. Book advertising is no exception. Malva Kemnitz's study focuses on advertising by West German publishers in the 1950s. Since publishing brochures were the outstanding advertising medium in the book industry at that time, aimed directly at the readers and thus the end customers, the advertising strategies of the publishers are analyzed on the basis of the cover design of their brochures. Taking into account previously unexplored image sources from the German Literature Archive in Marbach, production conditions, content and reception are examined in detail. The focus is on the central question of the publishers' imagination, their models, messages and motifs in a decade of upheaval between post-war and mass consumer society. The connection of quantitative approaches to content analysis with qualitative approaches to visual history opens up a more precise understanding of the interdependence of an opinion-forming group such as the publishing world with the educated middle class and the resulting effects on the design of the advertising material prospectus. Market strategies and target groups are presented convincingly in their historical context and allow a differentiated view of book advertising from the 1950s.